Anaerobic ability and explosive leg strength of youth female basketball players according to different position in the team - Stojmenovic, D.; Purkovic, N. T. M.; Stojmenovic, T. (Journal of Physical Education and Sport, 2023)
The primary objectives of the research are related to the examination of anaerobic capacity and explosive power of the legs young woman basketball players aged 14 to 16. The obtained values will be compared in relation to the positions (guard/forward/center) in the team. The hypothesis of the research refers to the fact that, due to the sensitivity of growth and development and consequently the sensitivity of developing motor skills in this period, there is no difference in anaerobic ability and explosive strength in basketball players according to positions in the team. The 48 female basketball players with an average age of 15.9±0.86 years participated in the study. The girls are divided into three groups of 16 players according to the position they play in the team. Anaerobic endurance was measured by the 300 yard shuttle test on the basketball court. Explosive power of standing vertical jump with hands on hips (counter movement jump - CMJ) was evaluated using a jumping platform (Globus Ergo Tester Platform). The platform is connected to a digital timer that records the time and height of the jump, and the power is estimated based on the reaction force of the surface and the duration of the flight phase. Statistical data processing (ANOVA) did not show any statistical significance regarding the differences in anaerobic endurance in girls in relation to the position in the team (p=0.714). In the case of the vertical jump, there was also no statistically significant difference (p=0.245). One of the reasons for the obtained results may be that there is no distinct selection in women's basketball at that age due to the insufficient number of girls who train basketball in the Belgrade region. Another reason why there is no statistically significant difference in the results is that early specialization is done in the younger categories, and some players have not reached the maximum in their development. Girls are placed in certain positions in relation to their basketball skills, and very rarely in relation to anthropological and motor skills.